Effect of the magnetotherapy in the regeneration after tenotomy in animals magnetotherapy in the regeneration - Grimaldo, Adrian Guilhermo Carrillo; Silva, Rodrigo Marcel Valentim da; Bezerra, Débora Antunes Pousa; Lima, Luíza Batista; Freire, Artur Dantas; Santos, Isafran Emanuelle dos; Senneke, Marcelo Alejandro; Meyer, Patrícia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The Achilles tendon is the largest and most resistant tendon in the human body, being one of the most common areas of overload injury among athletes. The rupture occurs more frequently in football athletes, running and jumping, because these activities cause a great stress on the tendon during eccentric muscle contraction of the sural triceps. Among the different physiotherapy resources used to repair tendon injuries, there is magnetotherapy, which is a feature that uses a pulsatile electromagnetic field, a suggested inducer of the acceleration of regeneration. Objective: To investigate the effects of magnetotherapy on the organization of collagen and elastic fibers and inflammatory process induced in different days and phases of the healing process of Achilles tendon injury in rats. Method: This study is a randomized controlled trial. Thirty female Wistar rats were randomly divided into 5 groups (each with n = 6), submitted to tenotomy by transverse shear in the middle third of the right Achilles tendon, except for group 1, which was control group without injury, sacrificed on day 14. Group 2, control with injury, sacrificed on day 7; group 3 was treated and received 5 pulsed electromagnetic field (PEMF) applications from 24h post injury and sacrificed on day 7; group 4, control with injury and sacrificed on day 14; and group 5 received 12 PEMF applications from 24h post injury and sacrificed on day 14. The parameters used were 20 mT, 50Hz and 30 minutes of application in each session, using the Magnetherp 330 digital device (Meditea). At the end of treatment, a histological study was performed to evaluate the amount of collagen and elastic cells and fibers and to compare the degree of organization of collagen fibers. Results: G - 3, compared to its control G - 2 showed lower acute inflammatory response; G - 5 did not show acute and chronic inflammation and possessed an accelerated process of repair without fibrosis, unlike its control. Conclusion: The magnetotherapy decreased the signs of inflammation in the acute phase, accelerated the repair process with the onset of fibrosis in 7 days; and at 14 days the tendon tissue was healed, with organizing fibrosis, without acute or chronic inflammation.